A control-oriented electrochemical model for lithium-ion battery. Part II: Parameter identification based on reference electrode. (February 2020) - Chu, Zhengyu; Jobman, Ryan; Rodríguez, Albert; Plett, Gregory L.; Trimboli, M. Scott; Feng, Xuning; Ouyang, Minggao
Highlights: A novel stepwise method that can identify the whole set of parameter values is proposed. The lumped-parameter model is reformulated mostly based on frequency decomposition. A reference electrode is included to achieve electrode decoupling Simulation and experiments are conducted for method validation. Abstract: Although electrochemical models have superior capabilities of internal states estimation to equivalent-circuit models, they have larger numbers of parameter values to be determined while predicting the behaviors of a real cell. Parameter identification of electrochemical models is essential but present methods are time-consuming and complex. In the "Part1" paper in this series, a lumped-parameter electrochemical model was built with the redundant/unobservable parameters removed. Using the this model, this paper proposes a novel stepwise method that can identify the whole set of parameter values for a physical cell using simple tests. The lumped-parameter model is specifically reformulated mostly based on frequency decomposition, and a reference electrode is included in the model to achieve electrode decoupling. The method is decomposed into four tests and eight steps, where the number of parameters to be identified in each step is significantly reduced, enhancing the computational efficiency and improving the identification accuracy. The identified values are first directly compared to the true values, and then the time-domain predictions of the lumped-parameter model using the identified values are compared to those of the full-order model using the true parameter values in terms of the terminal voltage and electrochemical states under different operation conditions.